Agile ETL - Xavier, Cristiano (2013)
Agile ETL is a tool for technicians working in the area of business intelligence, which facilitates consolidation of information in a central repository called data warehouse. Mechanisms have been established to create, control and monitoring processes of extraction transformation and loading of data, which is supposed to give a faster response either in creating or monitoring processes. ETL Framework can quickly integrate and consolidate data with good performance indicators.